ANALISIS KELAYAKAN USAHA DAN STRATEGI PENGEMBANGAN AGROINDUSTRI KERIPIK UBI KAYU NUABOSI MERK “QURENA” PADA KELOMPOK PKK DESA RANDOTONDA KABUPATEN ENDE - Willybrordus Lanamana; Laurentius Dominicus Gadi Djou; Kristono Yohanes Fowo; Yohanes Pande (Agriculture Faculty of Flores University, 2021)
This study aims to analyze the feasibility of the Nuabosi cassava chips agroindustry with the “Qurena” brand and formulate a strategy for its development. The research was conducted at the Home Industry for Processing Nuabosi Cassava with the brand